The Role of Acclimatization in Enhancing Athlete Performance in Extreme Environments - A Literature Review - Nimrot Manalu; Michael Mamio Lumbantobing; M. Aswin Sebayang; M. Nanda Natana Karokaro (Joska: Jurnal Isori Kampar, 2025)
Objectives: This review aims to examine the physiological mechanisms of acclimatization to extreme environments (heat, cold, and altitude) and evaluate their impact on athletic performance. Methods: A comprehensive literature search was conducted across major scientific databases including PubMed, Science Direct, and SPORTDiscus for studies published between 2000 and 2025. Selection criteria focused on research examining acclimatization protocols, physiological adaptations, and performance outcomes in extreme environmental conditions. Studies involving both elite and recreational athletes were included. Results: The analysis of 86 studies revealed that structured acclimatization protocols produce significant physiological adaptations specific to each extreme environment. Heat acclimatization enhances thermoregulation, cardiovascular efficiency, and fluid balance. Cold acclimatization yields modest benefits through metabolic and vascular adaptations. Altitude acclimatization improves oxygen transport and utilization through hematological and non-hematological mechanisms. The timing, duration, and specificity of acclimatization protocols significantly impact the magnitude of performance benefits across different sporting disciplines. Conclusion: Effective acclimatization strategies must be environment-specific, individualized, and systematically implemented to optimize athletic performance in extreme conditions. The integration of traditional and novel acclimatization approaches offers promising avenues for enhancing athlete resilience and competitive advantage in challenging environmental settings.